Chromophore attachment to fusion protein of streptavidin and recombinant allophycocyanin α subunit. Issue 1 (1st January 2018) - Wu, Jing; Chen, Huaxin; Jiang, Peng
ABSTRACT: The fusion protein (SLA) of streptavidin and allophycocyanin α subunit (holo-ApcA) was biosynthesized in Escherichia coli by a dual plasmid system. The recombinant SLA, purified by affinity chromatography, showed spectral properties similar to natural allophycocyanin α subunit (ApcA). Spectral and Zinc staining analysis indicated that the recombinant SLA covalently bound phycocyanobilin (PCB). To improve chromophorylation rate of recombinant SLA, an in vitro chromophore attachment reaction system was established, which contained partially chromophylated SLA, PCB and lyase CpcS. Spectral analysis showed that PCB bound to the recombinant SLA rapidly during the reaction. The chromophorylation rate of SLA was improved from 21.1% to 86.5%. Immunofluorescence assay showed that SLA with high chromophorylation rate had higher detection signal. Thus, in vitro chromophore attachment is an effective way to improve the chromophorylation rate of recombinant phycobiliprotein.